Faktor Yang Mempengaruhi Pendapatan Petani Tambak Ikan Di Desa Banjarsari Kecamatan Cerme Kabupaten Gresik - Aisyatu Rahma Hayati; Anita Handayani (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This research aims to identify factors that influence the income of fish pond farmers in Banjarsari Village, Cerme District. This research is a quantitative research involving a sample of 203 fish pond farmers from Banjarsari Village. The analysis technique used is multiple linear regression analysis technique. The results of the regression analysis show that the most influential variables in this research are work experience and land area, both of which have a positive and significant influence on farmer income. Meanwhile, the labor and selling price variables, although they have a positive influence, do not have a significant influence in this research.